STRATEGIC THINKING OF FUTURE TEACHERS IN A CHANGING CULTURAL AND EDUCATIONAL SPACE: REFINING THE CONCEPTUAL FRAMEWORK - Yuriy V. Shevchenko (Russian Journal of Education and Psychology)
Working with future teachers in new regions of the Russian Federation demonstrates the urgent need to update educational programs, fill social and educational trainings with new meanings, and form the content of education at universities. In this view, the elaboration of a system for the development of strategic thinking of future teachers, designed to interest them and ensure a high-quality educational process, is extremely in demand in the region due to the acute shortage of teaching staff.